Peningkatan Hasil Belajar Volume Balok Menggunakan Model PBL Kelas VB SDN Kuin Cerucuk 3 - Siti Rosidah; Sunarno (CV.ITTC INDONESIA, 2025)
The primary issue in this study is that fifth-grade pupils' learning outcomes in mathematics with reference to cuboid volume are subpar. A one-way learning approach, a dearth of successful learning models to boost student involvement, and low student engagement that makes learning dull and challenging are the culprits. The researcher suggests using the Problem-Based Learning (PBL) paradigm as a remedy. Classroom action research, which falls under the qualitative research category, was the methodology employed in this study. Both quantitative and subjective statistics are included in the offered content. The outcomes of student written examinations at the conclusion of each cycle provided quantitative data, while observation sheets of teacher and student behavior during the learning process provided qualitative data. This study was carried out at SDN Kuin Cerucuk 3 Banjarmasin during the even semester of class VB of the 2024–2025 academic year. Following two cycles, the results demonstrated that learning outcomes achieved a score of 100% using the conventional criterion of